A Study on Resources Mobilization in Turnaround/Shutdown Maintenance - Dhanaraj, Duraisamy; S, Saravanan (PT Larva Wijaya Penerbit, 2025)
Turnaround/shutdown maintenance (TAM) is a planned and periodic activity that involves the temporary shutdown of a production plant or equipment for inspection, repair, or replacement. TAM is essential for ensuring the reliability, safety, and efficiency of industrial facilities, especially in the oil and gas, petrochemical, and power sectors. However, TAM also poses significant challenges in terms of resources mobilization, scheduling, coordination, and cost management because TAM requires huge work forces including subject matter experts (SME), original equipment manufacturers (OEM), contractors, sub-contractors, and labors. Therefore, it is essential for minimizing the negative effects and maximizing the benefits of this resource’s mobilization strategy. This paper aims to explore the factors that influence the resources mobilization process in TAM and propose a framework for improving performance.